Elevated Baseline C-Reactive Protein as a Predictor of Outcome After Aneurysmal Subarachnoid Hemorrhage: Data From the Simvastatin in Aneurysmal Subarachnoid Hemorrhage (STASH) Trial. Issue 5 (November 2015) - Turner, Carole L.; Budohoski, Karol; Smith, Christopher; Hutchinson, Peter J.; Kirkpatrick, Peter J.
Abstract : BACKGROUND: There remains a proportion of patients with unfavorable outcomes after aneurysmal subarachnoid hemorrhage, of particular relevance in those who present with a good clinical grade. A forewarning of those at risk provides an opportunity towards more intensive monitoring, investigation, and prophylactic treatment prior to the clinical manifestation of advancing cerebral injury. OBJECTIVE: To assess whether biochemical markers sampled in the first days after the initial hemorrhage can predict poor outcome. METHODS: All patients recruited to the multicenter Simvastatin in Aneurysmal Hemorrhage Trial (STASH) were included. Baseline biochemical profiles were taken between time of ictus and day 4 post ictus. The t -test compared outcomes, and a backwards stepwise binary logistic regression was used to determine the factors providing independent prediction of an unfavorable outcome. RESULTS: Baseline biochemical data were obtained in approximately 91% of cases from 803 patients. On admission, 73% of patients were good grade (World Federation of Neurological Surgeons grades 1 or 2); however, 84% had a Fisher grade 3 or 4 on computed tomographic scan. For patients presenting with good grade on admission, higher levels of C-reactive protein, glucose, and white blood cells and lower levels of hematocrit, albumin, and hemoglobin were associated with poor outcome at discharge. C-reactive protein was found to be an independent predictor of outcome for patients presenting in good grade. CONCLUSION: Early recording of C-reactive protein may prove useful in detecting those good grade patients who are at greater risk of clinical deterioration and poor outcome. ABBREVIATIONS: ALP, alkaline phosphatase ALT, alanine aminotransferase CK, creatine kinase CRP, C-reactive protein EVD, external ventricular drainage ICH GCP, International Conference on Harmonisation guidelines for good clinical practice mRS, modified Rankin Scale SAH, subarachnoid hemorrhage STASH, Simvastatin in Aneurysmal Subarachnoid Hemorrhage Trial WBC, white blood cells WFNS, World Federation of Neurological Surgeons